Management of electric burn injury by NPWT, meshed skin graft and distant posterior thigh flap - Mohamed Sabry; AbdAllah Mahmoud Elsheikh; Abdou Mohamed Abd ALLAH. Darwish; Ahmed Abdou Mohamed; Ether Magdy Mahmoud; Ahmed Mohamed Saeed (Elsevier, 2022)
Background: Electric burn injuries can cause high morbidity and mortality. Case presentation: A 4.5-year-old child was admitted to our facility with deep full-thickness burns on the trunk and both lower limbs. After the patient's general condition was stabilized, numerous procedures were performed. A staged reconstruction resulted in stable coverage of the raw areas by meshed split thickness skin graft and distant posterior thigh flap. Nevertheless, the right limb below knee amputation had occurred. Conclusion: NPWT has a significant role in preparing the burned region for skin grafting, and the distant thigh flap remains a viable option in reconstructing the distal lower third of the leg.